The reconstruction of an hermitian Toeplitz matrices with prescribed eigenpairs - Liu Zhongyun (2010)
In this paper we concern the reconstruction of an hermitian Toeplitz matrices with prescribed eigenpairs. Based on the fact that every centrohermitian matrix can be re- duced to a real matrix by a simple similarity transformation, we rst consider the eigenstructure of hermitian Toeplitz matrices and then discuss a related reconstruction problem. We show that the di- mension of the subspace of hermitian Toeplitz matrices with two given eigenvectors is at least two and independent of the size of the matrix, and the solution of the reconstruction problem of an hermitian Toeplitz matrix with two given eigenpairs is unique.